Ambulatory blood pressure monitoring in patients with ST- elevation myocardial infarction: one year follow-up study - Nathani, Srikanth (International Journal of Research in Medical Sciences, 2019)
Background: The aim of this study was evaluation of nocturnal dipping of blood pressure in ST-elevation myocardial infarction (STEMI) patients and determining the effect of dipping on outcomes at 12 months follow-up. Methods: This was an observational, single-centre, retrospective study that included STEMI patients, performed in a tertiary care hospital in India from November 2016 to October 2017. The primary endpoint of the study was the assessment of outcomes at 12 months. The patients were divided into two groups on the basis of blood pressure dipping, i.e., patients with positive dipping were considered in group 1 and patients with negative dipping were considered in group 2. Results: Total 43 patients were included in the study. Group 1 consisted of 27 patients and Group 2 consisted of 16 patients. Mean 24 hr systolic blood pressure (SBP) and asleep SBP in Group 1 patients was 128.15±18.05 mmHg and 122.67±18.94 mmHg, respectively. Mean 24 hr diastolic (DBP) and asleep DBP in Group 1 patients was 78.07±10.73 mmHg and 73.41±12.35 mmHg, respectively. In the patients with non-dipping, mean 24 hr SBP and asleep SBP was 130.56±27.32 mmHg and 135.13±29.58 mmHg, respectively. Mean 24 hr DBP and asleep DBP was 76.00±15.40 mmHg and 79.69±17.05 mmHg, respectively. The mean percentage of asleep dipping of SBP was 5.7±6.7% in Group 1 and -4.6±6.82% in Group 2. Similarly, the mean percentage of asleep dipping of DBP was 7.6±9.0% in Group 1 and -6.3±9.1% in Group 2. Conclusions: In view of the results, it can be concluded that ambulatory blood pressure monitoring in patients with STEMI can provide a significant prognostication of the future events.